Towards personalized vaccines - Montin, Davide; Santilli, Veronica; Beni, Alessandra; Costagliola, Giorgio; Martire, Baldassarre; Mastrototaro, Maria Felicia; Ottaviano, Giorgio; Rizzo, Caterina; Sgrulletti, Mayla; Miraglia Del Giudice, Michele; Moschese, Viviana (Frontiers in Immunology, 2024)
The emergence of vaccinomics and system vaccinology represents a transformative shift in immunization strategies, advocating for personalized vaccines tailored to individual genetic and immunological profiles. Integrating insights from genomics, transcriptomics, proteomics, and immunology, personalized vaccines offer the promise of enhanced efficacy and safety, revolutionizing the field of vaccinology. However, the development of personalized vaccines presents multifaceted challenges, including technical, ethical, economic, and regulatory considerations. Addressing these challenges is essential to ensure equitable access and safety of personalized vaccination strategies. Despite these hurdles, the potential of personalized vaccines to optimize responses and mitigate disease burden underscores the significance of ongoing research and collaboration in advancing precision medicine in immunization.